Comment on F R Khan, S M R Kazmi, H K Siddiqui, et al. (J Pak Med Assoc. 2023; 73: 1275-1279) Prosthetic complications with dental implants: A bibliometric analysis of 20 top cited articles - Waseem Hassan (Journal of the Pakistan Medical Association, 2023)
Dear Editor, In June, 2023 Farhan et al., published an interesting short report.1 The authors explored the top 20 most cited articles on prosthetic complications with dental implants. They used Web of Science, and Google Scholar. Overall I enjoyed the article and the authors reported some interesting findings. However I have some observations and a few suggestions. Normally in bibliometric analysis proper search terms and strategies are defined along with or without boolean operators. The authors can also propose a particular time frame. Similarly in material and method section, it is normally elaborated if they searched the defined terms in titles, abstracts or keywords? For example based on the methods in the manuscript, several of searched-out articles do not contain the proposed keywords e.g. prosthetic complications in their titles. I will also not comment if the search keywords were appropriate or comprehensive. In table 1, the authors presented the authors, names of universities, countries, article type or study design. I could not understand why the same details were presented in table 2 and 3? These are some of the points which were a bit confusing and the guidance of Farhan et al., will be truly appreciated. Once again thanks for reporting a very interesting study.